Home Garden Eficiency in Kulon Progo District, Yogyakarta - Eka Lia Yusiana; Slamet Hartono; Irham Irham (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2016)
This study amis at determining factors that become source of yard farming inefficiency of both KRPL farmers (those who participated in Sustainable Food House Area program) and non KRPL farmers in Kulon Progo. Data Envelopment Analysis (DEA) was used with input and output-oriented assumptions to measure the efficiency score of yard farming observed. This Study showed that the sources of inefficiency in the yard farming were the excessive use of labor, cost and land area. Therefore, it should be adjusted with the number of workers to be reduced by 32%, farming cost by 31%, and the land area by 39%. Meanwhile, the output approach must be adjusted by adding 0.8% output for production and 1.17% for income.